Dengue and leptospirosis infection during the coronavirus 2019 outbreak in Sri Lanka. (6th April 2021) - Niriella, M A; Ediriweera, D S; De Silva, A P; Premarathna, B H R; Jayasinghe, S; de Silva, H J
Abstract: A significant decrease in dengue fever cases and a contrasting increase in leptospirosis cases were reported for the second quarter of 2020 compared with 2019 in Sri Lanka. In the absence of significant environmental and weather-related differences to account for these changes in incidence, we investigated the possibility that the effects of the COVID-19 pandemic on public health, social behaviour and the restrictions imposed during the lockdown influenced the fluctuations in dengue and leptospirosis infections.